If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4z = 20 Solving 8 + -4z = 20 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -4z = 20 + -8 Combine like terms: 8 + -8 = 0 0 + -4z = 20 + -8 -4z = 20 + -8 Combine like terms: 20 + -8 = 12 -4z = 12 Divide each side by '-4'. z = -3 Simplifying z = -3
| 4(z+7)-(2z-1)=z | | 8x-2x(x-9)=2(x-5)+1 | | X=-1-1*-1 | | 2/x-3=26/x | | 4(z+7)-(2x-1)=z | | 4c^2+19c-21=0 | | X=-8-1*-1 | | 16-(4M+8)=5+4M-13 | | (-1)-2*6= | | X=-8-y | | 3/4v=6 | | 6-8-(-12)-14-3*3*2*2= | | 5x+b=192 | | (-4)+(-2)*(-3)= | | 0=0.25x^2-5x+80 | | y=0.25x^2-5x+80 | | (-6)-(-10)= | | 0.8q+q=8(0.6q-2) | | 4x+2y+7+4x+3y= | | f(-1)=2x-3x | | 2x^2+x+1=25 | | 5y+y=90 | | 6-4(2-5x)= | | 8(m+3)=4 | | 11+5x=4x-20 | | log[2](-6-5x)=2 | | 8p^2-4p=o | | 4=2x^2-24x+76 | | x-8=4x+1 | | 2.50+5.75=56 | | log(5x-7)=3 | | (8.2h)/2=36.1 |